State feedback-based impedance control for legged robot hydraulic drive unit via full-dimensional state observer. (25th June 2020) - Zhu, Qixin; Yu, Bin; Huang, Zhipeng; Kang, Yan; Kong, Xiangdong; Ba, Kaixian
In this article, the hydraulic drive unit that drives the movement of the joint of a legged robot was researched, aiming at improving the control accuracy of the position-based impedance control system with dual input and single output. The state feedback control containing more state information of the system was adopted to replace the traditional output feedback and proportional-integral-derivative (PID) control, through the real-time calculation of the time-varying parameters of the servo valve flow, the nonlinear state space expression of the system was derived, the state feedback matrix and the input transformation amplifier were obtained and the full-dimensional state observer was designed. The experimental results show that the designed full-dimensional state observer can track the state variables of the actual system better. Compared with the traditional output feedback and PID control, state feedback control performs better in aspects of accuracy and system dynamics for the position-based impedance control system, which can further improve the compliance performance of the robot.